CORPORATE SOCIAL RESPONSBILITY (CSR) DAN ISLAMIC BANKING - SERVICE QUALITY (IB-SQ) SEBAGAI UPAYA PENGUATAN BRAND IMAGE DI LEMBAGA PERBANKAN SYARIAH - Ahmad Suminto; Nur Kasanah (WADIAH, 2021)
This library research method with a descriptive-analytic qualitativeapproach, aims to explain the urgency of Corporate Social Responsibility(CSR) and Islamic Banking - Service Quality (IB-SQ) as Efforts toStrengthen Brand Image in Islamic Banking Institutions. The resultsindicate that, the implementation of Corporate Social Responsibility (CSR)in Islamic banking institutions is a long-term investment, because theimplementation of the Corporate Social Responsibility (CSR) program willhave a positive impact not only on banking operations, but on thecontinuity of existence in future. Second, IB-SQ (Islamic Banking ServiceQuality) is the quality of service for Islamic banking in Indonesia whichcombines the term IB (Islamic Bank) with the term BSQ (Bank ServiceQuality) to identify service quality for the banking sector, so that the termIB-SQ is used for reflect the service quality and brand image for Islamicbanking in Indonesia.